2018
DOI: 10.1038/s41598-018-24933-8
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal two-photon imaging in somatosensory cortex of behaving mice reveals dendritic spine formation enhancement by subchronic administration of low-dose ketamine

Abstract: Ketamine, a well-known anesthetic, has recently attracted renewed attention as a fast-acting antidepressant. A single dose of ketamine induces rapid synaptogenesis, which may underlie its antidepressant effect. To test whether repeated exposure to ketamine triggers sustained synaptogenesis, we administered a sub-anesthetic dose of ketamine (10 mg/kg i.p.) once-daily for 5 days, and repeatedly imaged dendritic spines of the YFP-expressing pyramidal neurons in somatosensory cortex of awake female mice using in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Conversely, the somato-motor cortical regions displayed strain-specific increased degree, strength and betweenness centrality. As degree and strength signify number and weights of connections, this change may rather reflect an increased dendritic spine formation in the somatosensory cortex, reported in mice treated for 5 days with 10 mg/kg ketamine 44 .…”
Section: Strain-specific Effects Of Repeated Vs Single Ketaminementioning
confidence: 99%
“…Conversely, the somato-motor cortical regions displayed strain-specific increased degree, strength and betweenness centrality. As degree and strength signify number and weights of connections, this change may rather reflect an increased dendritic spine formation in the somatosensory cortex, reported in mice treated for 5 days with 10 mg/kg ketamine 44 .…”
Section: Strain-specific Effects Of Repeated Vs Single Ketaminementioning
confidence: 99%
“…9,11 These synaptic proteins produce an increase in dendritic spine density, and it is this proliferation of dendritic spines which is theorized to trigger the rapid antidepressant effect observed with ketamine administration. 13 Scientists have taken this thought one step further, however, and offered two theories describing how NMDA-receptor antagonism may result in the protein synthesis which is thought to stimulate synaptic activity in the corticolimbic structures. 14 One proposition is that these actions are achieved via selective antagonism in inhibitory interneurons, an action which then disinhibits cortical functions.…”
Section: Dr Bessel Van Der Kolk Makes Old Things New Again By Returnmentioning
confidence: 99%
“…This available glutamate then binds to AMPA (A‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid) receptors, precipitating a signal transduction cascade, which in turn activates another pathway that results in synaptic protein synthesis . These synaptic proteins produce an increase in dendritic spine density, and it is this proliferation of dendritic spines which is theorized to trigger the rapid antidepressant effect observed with ketamine administration …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that several signaling pathways play important roles in HC regeneration by inducing the proliferation and differentiation of SCs and Lg5+ progenitors. The up-regulation of canonical Wnt signaling induces the proliferation of sensory precursors in the postnatal mouse cochlea [3,4,[11][12][13][14][15][16][17], while Notch inhibition induces mitotic generation of HCs in the mammalian cochlea via activation of the Wnt pathway [12,14,[18][19][20][21][22][23][24][25]. Also, their effect on differentiation and the generation of HCs is related to important genes such as Atoh1 and Neurog1 [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%